ANALISIS PENGARUH LOYALITAS PEGAWAI TERHADAP KINERJA PEGAWAI DI PERUSAHAAN JASA MARITIM - Abid Tsabitul Azmi; Ristanti Akseptori; Danis Maulana (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
Based on the AKHLAK survey results Internalization Index employee loyalty in marine service companies can be said to be low because loyalty to the company falls into the category of Low Implementation Index with a percentage of 33.5%. The aim of this research is to analyze the influence of loyalty on employee performance. The sample in this study consisted of 137 permanent employees. This research uses a quantitative approach with data collection techniques using questionnaires and interviews. Hypothesis testing uses simple linear regression analysis. Hypothesis testing results show nilai p-value of the employee loyalty variable is 0 or p-value < 0.05. This means that employee loyalty has a positive and significant effect on employee performance in maritime service companies in Surabaya. Companies need to make efforts to foster loyalty so that they can improve performance.